2022
DOI: 10.1371/journal.pcbi.1009827
|View full text |Cite
|
Sign up to set email alerts
|

Traveling waves in the prefrontal cortex during working memory

Abstract: Neural oscillations are evident across cortex but their spatial structure is not well- explored. Are oscillations stationary or do they form “traveling waves”, i.e., spatially organized patterns whose peaks and troughs move sequentially across cortex? Here, we show that oscillations in the prefrontal cortex (PFC) organized as traveling waves in the theta (4-8Hz), alpha (8-12Hz) and beta (12-30Hz) bands. Some traveling waves were planar but most rotated. The waves were modulated during performance of a working … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 45 publications
8
60
0
Order By: Relevance
“…This interpretation is also consistent with earlier work showing that different patterns of neuronal oscillations modulate feedforward networks during visual perception 51,54 and as well as feedback processing during top-down control and prediction 55 . Consistent with our results, there is also other evidence of neural activity changing direction for specific functional states 25,44,[56][57][58][59][60] , thus suggesting that our results are part of a broader phenomenon.…”
Section: Discussionsupporting
confidence: 92%
“…This interpretation is also consistent with earlier work showing that different patterns of neuronal oscillations modulate feedforward networks during visual perception 51,54 and as well as feedback processing during top-down control and prediction 55 . Consistent with our results, there is also other evidence of neural activity changing direction for specific functional states 25,44,[56][57][58][59][60] , thus suggesting that our results are part of a broader phenomenon.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that TWs were strongest in the beta frequency band (10–30 Hz) is consistent with a long line of work linking frontal beta-band oscillations with cognitive control and working memory (Babapoor-Farrokhran et al, 2017; Bhattacharya et al, 2022; Brincat and Miller, 2015; Miller et al, 2018; Womelsdorf, 2021). Studies have also suggested that beta-band oscillations behave as propagating TWs in sensory, motor and premotor structures (e.g., in humans ((Stolk et al, 2019; Takahashi et al, 2011), monkeys (Rubino et al, 2006; Takahashi et al, 2015), and cats (Roelfsema et al, 1997))).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, rather than being uniformly distributed, TWs propagated primarily along two directions aligned with one spatial axis. This pattern may indicate preferential connectivity along anatomical axes orthogonal to a sulcus (Rubino et al, 2006) or, alternatively, may be due to the fact that our microarrays provided a narrow view, through a ∼10 mm 2 aperture, into what may have been a more complex (e.g., spiral or circular) pattern over larger cortical areas (Bhattacharya et al, 2022; Ermentrout and Kleinfeld, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Propagating wave activity can occur in a wide range of different speeds, with propagation speeds broadly falling into two categories. Speeds for mesoscopic traveling waves occurring within cortical columns and their lateral connections, as identified using local field potential (LFP), multielectrode arrays or optical imaging, and range between 0.1-0.8m/s (Bhattacharya et al, 2022; Rubino et al, 2006; Takahashi et al, 2011, 2015). These slower wave speeds are consistent with axonal conduction speeds of unmyelinated horizontal fibres in the superficial layers of the cortex (Girard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%